Pedagogical approaches to improving the military training system with regard to the current challenges - Shemchuk, Vadym; Kabitska, Oksana; Skrypka, Oleksandr; Svoboda, Ivo; Danylevskyi, Andrii (Perspectivas em Diálogo: Revista de Educação e Sociedade, 2025)
This research highlights the urgent need to modernize military training for contemporary instability and technological progress. The study aimed to adapt pedagogical approaches to address technological and psycho-emotional challenges. Methods involved a pedagogical experiment using case studies and monitoring with specific inventories. Statistical analyses confirmed the effectiveness of these methods. Experimental Group 1 significantly excelled in performance and soft skills, with lower stress. Other experimental groups showed improvement, though some stress remained. The control group had the lowest results, emphasizing the need for innovation. The study concludes that modern pedagogical approaches, especially technology integration, enhance academic performance, develop soft skills, and reduce stress. Future research should refine these approaches, focusing on technology, psychological resilience, and teamwork.